Strategi Pembelajaran Perguruan Tinggi di Era Artificial Intelligence (AI) - Mubarok, Najib; Susanti, Eri; Lestari, Elva (STAI Darul Kamal NW Kembang Kerang, 2024)
The aim of this research is to find out a quantitative descriptive picture of the skills of PTKI lecturers in Indonesia and formulate strategies in dealing with the invasion of Artificial Intelligence (AI) in higher education. Based on the type of data, this research is mixed research (Mixed Method Research). The research framework chosen is a case study. Data collection techniques use questionnaires, Online Focus Group Discussion (OFGD), observation and documentation. From the results of data analysis, it is known that the majority of lecturers have a level of skill and readiness in facing AI invasion on a scale of 3 from 1 to 5. Furthermore, it is concluded from the comparison test that lecturers over 42 years old have a significantly lower level of skill and readiness than the next generation. . Meanwhile, from qualitative analysis it is concluded that AI can improve the quality and efficiency of learning systems if AI is positioned as a tool. If adaptation to the AI ​​era is not carried out, AI will actually become a new disruption in learning in higher education.